2021
DOI: 10.3389/fmars.2021.562267
|View full text |Cite
|
Sign up to set email alerts
|

Lateral, Vertical, and Temporal Variability of Seawater Carbonate Chemistry at Hog Reef, Bermuda

Abstract: Spatial and temporal carbonate chemistry variability on coral reefs is influenced by a combination of seawater hydrodynamics, geomorphology, and biogeochemical processes, though their relative influence varies by site. It is often assumed that the water column above most reefs is well-mixed with small to no gradients outside of the benthic boundary layer. However, few studies to date have explored the processes and properties controlling these multi-dimensional gradients. Here, we investigated the lateral, ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 82 publications
2
5
1
Order By: Relevance
“…The DO ranges recorded at our sites 30.7 μmol/L at Goff's Caye fore reef (30.0 μmol/kg), 32.0 μmol/L at Goff's Caye back reef (31.3 μmol/kg), 11.9 μmol/L at English Caye (11.6 μmol/kg), and 7.6 μmol/L in Dominica (7.4 μmol/kg) are generally lower than those reported in other studies (e.g., 22-54 μmol/kg in Bermuda (Pezner et al, 2021;Takeshita et al, 2018) and in Puerto Rico 60 μmol/L (fall) and 120 μmol/L (winter) (Gray et al, 2012)).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…The DO ranges recorded at our sites 30.7 μmol/L at Goff's Caye fore reef (30.0 μmol/kg), 32.0 μmol/L at Goff's Caye back reef (31.3 μmol/kg), 11.9 μmol/L at English Caye (11.6 μmol/kg), and 7.6 μmol/L in Dominica (7.4 μmol/kg) are generally lower than those reported in other studies (e.g., 22-54 μmol/kg in Bermuda (Pezner et al, 2021;Takeshita et al, 2018) and in Puerto Rico 60 μmol/L (fall) and 120 μmol/L (winter) (Gray et al, 2012)).…”
Section: Discussioncontrasting
confidence: 61%
“…More recently, mean daily DO concentrations and ranges from 32 reefs around the globe have been reported as 173 ± 28 μmol/kg and 81 ± 52 μmol/kg respectively (Pezner et al, 2023). The greater DO amplitudes reported in the literature do not always correspond to greater pH ranges (0.067 (winter) and 0.093 (fall) in Puerto Rico (Gray et al, 2012) and 0.07 at Hog Reef (Pezner et al, 2021;Takeshita et al, 2018)) and could imply different biogeochemical and metabolic regimes, reflecting variations in benthic ecosystem compositions. Minimum DO values recorded at English Caye and Goff's Caye (both fore reef and back reef sites) were on occasion below 156 μmol/L, a threshold below which reef ecosystems are considered "weakly hypoxic" and therefore under stress (Vaquer-Sunyer & Duarte, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-sample t-tests performed at each site indicated that mean flow speed did not differ significantly between day and night (p > 0.6, Table S4 in Supporting Information S1) suggesting that mean primary production rates during the day were greater than mean respiration rates at night and the Onna-son reef system was net autotrophic throughout the study period. Although calcification and CaCO 3 dissolution also affect seawater pH, they do not directly affect DO concentrations, and rates and variability of organic carbon cycling on reefs are typically greater than rates and variability of net community calcification over the diel timescales considered in this study (Cyronak et al, 2018;Pezner et al, 2021;Takeshita et al, 2018).…”
Section: Diel Variation In Ph and Dissolved Oxygen In Relation To Par...mentioning
confidence: 81%
“…Calcification and CaCO 3 dissolution decrease and increase pH, respectively, with no direct influence on DO. These processes occur within both benthic and water column communities (Kinsey, 1985; Pezner et al., 2021; Smith et al., 2013; Tilstra et al., 2018). The degree to which the biogeochemistry of reef seawater is modified depends on the relative rates of these processes, which vary over diel (Gruber et al., 2017; Kekuewa et al., 2021) and seasonal timescales (Davis et al., 2020; Page et al., 2019), and the benthic communities modifying the overlying seawater (e.g., seagrass, seaweed, sand, rubble, and corals; Jokiel et al., 2014; Page et al., 2016).…”
Section: Introductionmentioning
confidence: 99%